posted by .

solve and check each of the following quadratic equation
(1)x^+x-6=0
(2)x^+8x+15=0
(3)x^+2x+1=0
(4)x^-3x-4=0
(5)x^-4x-32=0

1) x= -3 or x = -2
2)x= -3 or x= -8
3) x=-1
4) x=4 or x=-1
5) x=8 or x=-4

Hope that helps.

:)

## Similar Questions

1. ### Algebra2

Find the polynomials roots to each of the following problems: #1) x^2+3x+1 #2) x^2+4x+3=0 #3) -2x^2+4x-5 #3 is not an equation. Dod you omit "= 0" at the end?
2. ### algebra II

I'm quite clueless as to how to solve this. I know the quadratic equation but am not sure how to get this equation into the format to plug in to the quadratic... Solve the quadratic equation using the formula [1/(1+x)]-[1/(3-x)]=(6/35) …
3. ### Algebra

Solve the quadratic equation. 3x^2-15x+18=0 I know that the formula to quadratic equation is x=-b+and-(square root)b^2-4ac divided by 2a. I know that a=3, b=-15 and c=18, then subsitute in and get two answers, my problem is that I …
4. ### algebra

0. Tell your classmates about your pet to set up the scenario for fencing a rectangle in your yard. 1. You MUST start by choosing an amount of area that you want to fence in for your pet and this MUST be stated first. What amount of …

solve and check each of the following quadratic equation (1)x^-9x=0 (2)x^+8x=0 (3)x^=6x (4)x^=-3x
6. ### help in math

solve and check each of the following quadratic equation (1) x^2=6x (2) x^2=3x (3)x^2=17x (4) x^2=5x+6 (5) x^2+9x=10
7. ### math

solve and check each of the following quadratic equation (1)x^2+16x=36 (2)x^2=10x-16 (3)3x=x^2-4
8. ### math

Jenny wanted to solve the quadratic equation x2 - 11x +18 = 0 by factoring. Which of the following equations would lead her to solve the given equation?
9. ### math

Heather is solving an equation by graphing the expressions on both sides. If her graph intersects at an infinite number of points, which statement could describe the equation Heather is attempting to solve?
10. ### Pre-Calc

Solve the quadratic equation by factoring. Check your solutions in the original equation. (Enter your answers as a comma-separated list.) x^2 + 2ax + a^2 = 0

More Similar Questions